2008
DOI: 10.1161/circresaha.108.178756
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Cellular Uptake of Remnant High-Density Lipoprotein Particles

Abstract: Abstract-A low level of high-density lipoprotein (HDL) cholesterol is characteristic of insulin resistance and hypertriglyceridemia and likely contributes to the increased risk of cardiovascular disease associated with these conditions. One pathway involves enhanced clearance of lipolytically modified HDL particles, but the underlying mechanisms remain poorly understood. Here, we examine the effect of triglyceride enrichment and hepatic lipase hydrolysis on HDL binding, internalization, and degradation in cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Our observation that the hyperalphalipoproteinaemic participants have increased post-heparin lipoprotein lipase activity and diminished hepatic lipase activity compared with the hypoalphalipoproteinaemic participants is in agreement with a previous report [41]. Due to the high-HDL insulin-sensitive state in hyperalphalipoproteinaemia binding and internalization rates of triglyceride-enriched HDL may slow down [42]. Thus, our results conform to the following chain of events described in a previous review [43].…”
Section: Discussionsupporting
confidence: 93%
“…Our observation that the hyperalphalipoproteinaemic participants have increased post-heparin lipoprotein lipase activity and diminished hepatic lipase activity compared with the hypoalphalipoproteinaemic participants is in agreement with a previous report [41]. Due to the high-HDL insulin-sensitive state in hyperalphalipoproteinaemia binding and internalization rates of triglyceride-enriched HDL may slow down [42]. Thus, our results conform to the following chain of events described in a previous review [43].…”
Section: Discussionsupporting
confidence: 93%
“…CETP transports CE from HDL to VLDL in exchange for TG. The TG-enriched HDL is susceptible for hepatic lipase activity, which can result in the formation of HDL remnants like the lipid-poor pre ␤ -1 and ␣ -4 particles ( 34 ). As a result of a decrease in HDL size, the fractional catabolic rate of HDL increases ( 35 ), which may provide a possible explanation for the lower baseline levels of key HDL components (HDL-C, apoA-I, and apoA-II) in obese subjects.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation proposed by Xiao et al [35] demonstrated that compared to native and TG-rich HDL, the binding of remnant HDL was markedly higher in both HepG2 cells and HEK293 cells. Remnant HDL was internalized to a greater extent in both cell types and was more readily degraded in HEK293 cells.…”
Section: Changes In Hdl Componentmentioning
confidence: 99%